Meat Production Practices in Slaughterhouse and Retail Meat Shops in Bareilly District of Uttar Pradesh - Sahay, Anupam; Tiwari, Rupasi; Sharma, M C; Roy , Rakesh (Journal of Meat Science, 2011)
The present study was taken up in Bareilly district of Uttar Pradesh to analyze the meat processing and production practices in the slaughter houses and retail meat shops. Twenty butchers of large animal slaughterhouse (LAS), ten butchers of small animal slaughterhouse (SAS) and thirty meat retailers were randomly selected for the study. Results of the study revealed that majority of butchers were illiterate, with 5 to 15 years of experience, medium work load and without formal training. Various factors for unhygienic meat production include social backwardness, low income, poor personal hygiene, and poor state of existing buildings of LAS and SAS. Retail meat shops lacked essential facilities. Majority of meat handlers were unaware to the public health hazards due to unhygienic meat. The study reveals that there is an urgent need of creating awareness among all the stakeholders of meat production viz. livestock owners, butchers and retailers regarding meat hygiene and associated health hazards.